The effects of community income inequality on health: Evidence from a randomized control trial in the Bolivian Amazon. (January 2016) - Undurraga, Eduardo A.; Behrman, Jere R.; Leonard, William R.; Godoy, Ricardo A.
Abstract: Research suggests that poorer people have worse health than the better-off and, more controversially, that income inequality harms health. But causal interpretations suffer from endogeneity. We addressed the gap by using a randomized control trial among a society of forager-farmers in the Bolivian Amazon. Treatments included one-time unconditional income transfers (T1 ) to all households and (T2 ) only to the poorest 20% of households, with other villages as controls. We assessed the effects of income inequality, absolute income, and spillovers within villages on self-reported health, objective indicators of health and nutrition, and adults' substance consumption. Most effects came from relative income. Targeted transfers increased the perceived stress of participants in better-off households. Evidence suggests increased work efforts among better-off households when the lot of the poor improved, possibly due to a preference for rank preservation. The study points to new paths by which inequality might affect health. Highlights: Does community income inequality harm individual's health? We used a randomized control trial in an Amazonian society of forager-farmers. We gave income transfers to the poorest and to all households in randomized villages. Evidence suggests increased work efforts among better-off when the poor improve. Our study highlights paths by which income inequality might affect health.